Designing and Researching Virtual Learning Communities - Santos, Antonio (International Journal of Emerging Technologies in Learning (iJET), 2012)
This article describes, with a basis in educational literature, some of the main characteristics of learning communities. In addition, a list of instructional strategies is proposed to create a virtual learning community within a traditional academic course. These strategies are then integrated into a proposed research design to study and evaluate this particular type of learning and know what questions to ask, what data to collect, and how to analyze them.